Rationally designed CuFe2O4-mesoporous Al2O3 composite towards stable performance of high temperature water-gas shift reaction - Subramanian, Vijayanand; Gnanakumar, Edwin S.; Jeong, Dae-Woon; Han, Won-Bi; Gopinath, Chinnakonda S.; Roh, Hyun-Seog (Chemical Communications, 2013)
High temperature water-gas shift reaction was demonstrated for the first time on a CuFe2O4-mesoporous alumina nanocomposite between 350 and 550 degrees C with 70-80% CO-conversion using simulated waste derived syngas under realistic conditions. Despite high Al-content, the catalyst exhibited stable activity, which was attributed to the nano-architectured robust porous nature of alumina integrated with surrounding CuFe2O4.